INVESTIGATING THE LONGITUDINAL RELATIONSHIP BETWEEN CARDIOMETABOLIC CONDITIONS AND LONELINESS IN OLDER PEOPLE. (16th November 2018) - Smith, K; Victor, C
Abstract: The aim of this work was to determine the direction of association between coronary heart disease, stroke or diabetes with loneliness using 14-years of follow-up data. Data was taken from the English Longitudinal Study of Ageing, a prospective cohort study of adults aged ≥ 50 years in England. Wave 2 served as baseline, and participants were followed up to Wave 8. Loneliness was determined using the short UCLA-loneliness scale. Stroke, diabetes and coronary heart disease (CHD) were determined using self-reported diagnosis. Data were analysed using Cox hazards regression with time-varying predictors (adjusted for relevant baseline sociodemographic, health and psychological confounders). We did not find that loneliness was not a risk factor for incident stroke, whereas stroke was a risk factor for incident loneliness (HR 1.57: 1.12–2.22). There was evidence for an unadjusted bi-directional association between diabetes and loneliness, however after adjusting for confounder's only the relationship from diabetes to incident loneliness remained significant (HR 1.30: 1.08–1.56). Finally, we found that loneliness had an unadjusted association with incident CHD but that adjustment for confounders attenuated this relationship. We found no evidence that CHD had an association with incident loneliness. Our results indicate that there is a complex longitudinal relationship between cardiometabolic conditions and loneliness. We found that stroke and diabetes were risk factors for loneliness, and that any relationship between loneliness with incident CHD or diabetes was attenuated after adjusting for confounders. This work emphasises the need to consider loneliness as a consequence of cardiometabolic conditions.